Manfaat Media dalam Keberlangsungan Dakwah - Efendi, Erwan; Julyanda, Fanny; Warohmah, Wina; Nasution, Aswani; Septianto, Cahyo (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Currently, the development of science and technology is increasingly rapid. Reform efforts in the application of technological achievements were carried out in various fields, especially in the mission sector. Media is a tool or means used by society to convey information. In this context, the use of media is very important to make it easier for people to convey important messages. For this reason, missionaries have developed new strategies that use digital and non-digital media to convey missions.In this article, we focus on libraries. In this modern era, many missionaries use technological media to spread missions to various groups, not only within the country but also abroad to all corners of the world.